Vector Nature of Dissipative-Soliton-Resonance Pulses in Fiber Lasers Mode-Locked by Nonlinear Polarization Rotation Technique - Wenxiong Du; Heping Li; Junwen Li; Zhuang Wang; Pinghe Wang; Zhiyao Zhang; Yong Liu (IEEE Photonics Journal)
The vector nature of dissipative-soliton-resonance (DSR) pulses is numerically investigated in an all-normal-dispersion Yb-doped fiber laser mode-locked by the nonlinear polarization rotation technique. We calculate the polarization ellipses of the DSR pulse throughout the cavity, which shows that the polarization state varies during the propagation. The features of pulse polarization are also displayed on the Poincaré sphere. The impact of nonlinear birefringence on the polarization evolution is analyzed. Furthermore, we find that the polarization state is not uniform across a DSR pulse at a fixed intracavity position. The flat-top part of the pulse has a nearly fixed polarization, while its leading and trailing edges feature polarization states that vary with time. The peak power ratio of the two orthogonal polarization components in the pulse is limited in the range from 4 to 31. Our simulation results offer insight into the polarization properties of DSR pulses in mode-locked fiber lasers containing polarization discrimination devices.